2020
DOI: 10.3390/rs12233873
|View full text |Cite
|
Sign up to set email alerts
|

UAS-Remote Sensing Methods for Mapping, Monitoring and Modeling Crops

Abstract: The advances in Unmanned Aerial Vehicle (UAV) platforms and on-board sensors in the past few years have greatly increased our ability to monitor and map crops. The ability to register images at ultra-high spatial resolution at any moment has made remote sensing techniques increasingly useful in crop management. These technologies have revolutionized the way in which remote sensing is applied in precision agriculture, allowing for decision-making in a matter of days instead of weeks. However, it is still necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In [7] investigated that agri-food industries have increased with the aim of improving productivity by at least 70%. Precision agriculture (PA) has greater potential and is made possible by new methods of data analysis that reveal patterns and trends as well as emerging technologies like the Internet of Things (IoT).…”
Section: Introductionmentioning
confidence: 99%
“…In [7] investigated that agri-food industries have increased with the aim of improving productivity by at least 70%. Precision agriculture (PA) has greater potential and is made possible by new methods of data analysis that reveal patterns and trends as well as emerging technologies like the Internet of Things (IoT).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, UAVs have been widely used in the last 30 years in precision agriculture [12]. A comprehensive review on UAV-based applications in precision agriculture can be found in [1,[4][5][6][7][8][9][10][11][12][13], and several UAV onboard sensors for remote sensing are reviewed in [14]. Deployment of any UAV application involves the integration of several issues.…”
Section: Introductionmentioning
confidence: 99%